Juvenile Anadromous Salmonid Production in Upper Columbia River Side Channels with Different Levels of Hydrological Connection. Issue 3 (30th April 2014) - Martens, Kyle D.; Connolly, Patrick J.
Abstract: We examined the contribution of three types of side channels based on their hydrologic connectivity (seasonally disconnected, partially connected, and connected) to production of juvenile anadromous salmonids. Juvenile steelhead Oncorhynchus mykiss and Chinook Salmon O. tshawytscha were found in all three of these side channel types and in each year of the study. Upon connection with the main stem at high flows, the seasonally disconnected side channels experienced an emptying out of the previous year's fish while filling with young‐of‐year fish during the 2‐ to 4‐month period of hydrologic connection. There were no differences between the densities of juvenile steelhead and Chinook Salmon and the rate of smolts produced among the three types of side channels. Recently reintroduced Coho Salmon O. kisutch had sporadic presence and abundance in partially and connected side channels, but the smolt production rate was over two times that of steelhead and Chinook Salmon in seasonally disconnected side channels. Within seasonally disconnected side channels, young‐of‐year salmonids in deep pools (≥100cm) had greater survival than those in shallow pools (<100cm). Densities of juvenile steelhead in all side channel types were similar to those in tributaries and were higher than in main‐stem lateral margins. Juvenile Chinook Salmon densities were higher in side channels than in both tributary and main‐stem lateral margins. Our results suggest that improving quality of pool habitat within seasonally disconnected side channels can result in improved survival for juvenile anadromous salmonids during the period of disconnection. Habitat improvement in these seasonally disconnected side channels should be recognized as a worthy restoration strategy, especially when full connectivity of side channels may not be a feasible target (e.g., through lack of water availability) or when full connectivity may present too high a risk (e.g., flooding, stream capture, bank destabilization).